Preservation of semen from Kintamani Bali dogs by freezing method (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: To explore the effect of glycerol at different concentrations using different extenders on DNA fragmentation and motility of frozen-thawed Kintamani Bali dog spermatozoa.Materials and Methods: Sample was collected from four mature Kintamani Bali dogs. Each ejaculate was prepared for cryopreservation with two different semen extenders; egg yolk Tris extender and coconut water-based extender. For each extender, three different glycerol concentrations were used; 4%, 6%, and 8%. Each of the six aliquots was loaded into 0.5 ml cryotube, placed on a styrofoam box 5 cm over liquid nitrogen for 10 min, and immersed in liquid nitrogen up to 8 min. Then, the frozen cryotubes were transferred into liquid nitrogen container. The cryotubes were thawed in a water bath at 38.5°C for 120 sec. After equilibration and thawing, each sample was assessed for motility parameters and for DNA fragmentation.Results: The addition of 6% glycerol to extenders revealed the most effective addition of glycerol on motility and sperm DNA fragmentation after equilibrium and post-thawing.Conclusion: It is concluded that both extenders with the addition of 6% glycerol are safe to be used as an extender in Kintamani Bali dog semen preservation, and DNA fragmentation of Kintamani Bali dog spermatozoa was not influenced by the freezing procedure.J. Adv. Vet. Anim. Res., 6(2): 158-162, June 2019